Production of bulk NV centre arrays by shallow implantation and diamond CVD overgrowth (Phys. Status Solidi A 10∕2016). Issue 10 (13th October 2016) - Lesik, Margarita; Raatz, Nicole; Tallaire, Alexandre; Spinicelli, Piernicola; John, Roger; Achard, Jocelyn; Gicquel, Alix; Jacques, Vincent; Roch, Jean‐François; Meijer, Jan; Pezzagna, Sébastien
Abstract : The nanometre‐scale engineering of single nitrogen‐vacancy (NV) centres in diamond can be obtained by nitrogen implantation only at low‐energy (keV) with limited straggling. However, shallow NV centres (a few nm deep) generally have inferior overall properties than deeply implanted or deep native NV centres, due to the surface proximity. The study by M. Lesik et al. (pp.2594–2600 ) shows the successful overgrowth of a pattern of very shallow implanted (2 nm) NV centres using an optimised overgrowth process, resulting in a bulk‐like array of NV centres 4 ìm below the surface. A pierced AFM tip has been used to collimate the ion beam during the nitrogen implantation. The growth conditions have been tuned to reduce at most surface etching and passivation of the implanted NV centres at the overgrowth start. Furthermore, the charge state of ensembles and single NV centres is stabilised in the wished negative charge state NV − after overgrowth. The combination of low‐energy high‐resolution ion implantation and high‐purity chemical vapour deposition (CVD) overgrowth procedures opens the way towards the fabrication of scalable and efficient quantum devices based on single defects in diamond.